The intensification of the use of screens and repercussions on children's neuropsychomotor development (Research, Society and Development, 2024)
Objective: To evaluate the relationship between screen time and delays in neuropsychomotor development. Methodology: Children aged 0 to 12 years old, treated at a pediatric outpatient clinic were assessed. A questionnaire was applied to highlight screen time, the age at which neurological development milestones occurred, sex, age, gestational and prenatal data, social status, maternal education, and personal morbid history. Children with pathologies that affect neuropsychomotor development were excluded. The Denver II scale, Minimental State Examination, Language Milestones, and Vygotsky Test were applied in neurological development evaluation. Results: 35 children were included. Intensified use of screens was observed in 88.7%, of which 13.8% in the age group (0-23 months and 29 days), 16.6% (24-59 months and 29 days), and 58.3 (60 to 144 months). The Denver II test applied to children aged 0 to 60 months showed that 38.4% had delayed psychomotor development. The Minimental applied to 18 children over 72 months showed delayed psychomotor development in 50%. Of the 35 children assessed, 40% had delayed psychomotor development and of these, 78.6% had increased use of screens as a risk factor. Conclusions: The study showed an increase in hours spent using screens in the age group studied, being more intensified in the age group over 60 months, and that this factor, having ruled out other interfering variables, may be implicated in the high percentage of children with delay found in the study.